OPTIMUM FISCAL SPENDING AT AGGREGATED AND DISAGGREGATED LEVEL IN PAKISTAN - Aysha Qamar; Ghulam Ghouse; Aribah Aslam; Sana Raza; Aysha Aziz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study analyzed the relation between public spending and economic growth. Endeavors have been made to check whether or not there is any inverted U shape connection between government expenditures and economic growth. In theory, the connection amongst optimum government expenditures and economic growth has been linked with the Armey Curve. Armey curve shows the role of government in economic activities. The simple reason at the back of Armey curve is that the relation among government expenditures and growth is positive until it reaches a specific point, after that this link turns into negative. In this study the optimum level of government expenditures for various categories such as development spending, current spending (non-development) and overall government spending which maximize economic growth are calculated. The results show that, given the present structure of the economy, the maximum size of overall government spending, current spending & development spending are 22.41 %, 14% & 8.3 % of GDP, respectively. It may be noted that tax to GDP ratio need to be enhanced, development expenditures need to be significantly improved and current expenditures need to be curtailed, if at all Pakistan has to put on the path of sustainable economic growth. Pakistan is far away from the optimal expenditures listed above. Its economic performance is very poor at present. JEL Classification: E62, C20, P16, O40